Commercialization, Renewal and Quality of Patents - Roger Svensson (Research Institute of Industrial Economics (IFN), 2011)
One of the major reasons why inventors are awarded patents by governments is they encourage R&D investments and commercialization of inventions. If the patent holder commercializes his invention, he has stronger incentives to retain the patent. The purpose here is to empirically analyze the relationship between commercialization and the renewal of patents. At the same time, I take into account defensive patent strategies (e.g. deterring competitors from utilizing the patent) and pointedly ask if there are any third factors (quality of the patent) that affect the commercialization and renewal decisions. Using a detailed database of Swedish patents, I utilize a survival model to estimate how commercialization influences the patent renewal decision. Basic results show commercialization and defensive strategies increase the probability a patent will be renewed, but also that quality influences commercialization and renewal decisions. When controlling for endogenous commercialization decision, there is still a strong positive relationship between commercialization and renewal of patents. Thus, given the quality of the patent, if the owner decides to commercialize the patent on the margin, this leads to longer survival of the patent. With regard to commercialization modes, there is some evidence licensed patents and patents commercialized in original and new firms but not acquired patents survive longer than non-commercialized patents. Looking more closely at the contracts of acquired and licensed patents, contracts with both variable and fixed fees but not contracts with either variable or fixed fees survive longer than non-commercialized patents. However, the analysis about modes and contract terms does not take into account the endogeneity problem.
Keywords: L24; O31; O34; 330; Patents; Renewal; Commercialization; quality; Commercialization modes; Contract terms; Survival models; Patent; Forschungsfinanzierung; Kommerzialisierung; KMU; Schweden